Environmentally friendly Fe3+-activated near-infrared-emitting phosphors for spectroscopic analysis - Wang, Jing (Light, science & applications, 2022)
Highly efficient Fe 3+ -activated Sr 2- y Ca y (InSb) 1- z Sn 2 z O 6 broadband near-infrared-emitting phosphors with tunable emission from 885 to 1005 nm are developed as alternative for primarily studed toxic Cr 3+ -activated near-infrared-emitting phosphors for application in spectroscopy analysis.